Bentuk dan Makna Slang Program Lapor Pak di Kanal YouTube Trans7 Periode Januari 2026: The Form and Meaning of Slang for the Lapor Pak Program on the Trans7 YouTube Channel for the January 2026 Period - Ayu Yulianti; Ediwarman Ediwarman; Agus Iryana (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2026)
Slang is a social variation used by certain groups that is very limited, flexible, and typically contemporary. Slang is increasingly widespread in the digital era, with many social media videos using it. Lapor Pak! is a comedy program on the Trans7 YouTube channel that features many slang terms. This study uses a qualitative descriptive method. Data collection techniques are through documentation studies and field notes. Data analysis techniques in this study include data reduction, data presentation, and drawing conclusions or verification. The results of the data in this study are in the form of expressions or utterances expressed by comedians in the Lapor Pak! comedy program. The results of this study include 14 slang data, classified into 4 forms of slang according to Bloomfield, in the Lapor Pak! Comedy Program on the Trans7 YouTube channel during the period of January 2026.The abbreviations found include DP, COD, and CEO. The forms of funny mispronunciations found include, among others, dompet pesek, jobder, usus bantu, Dian Sosro, and narcoboy. The shortened forms found include Irjen, bansos, loker, and Kombes. Three forms of slang were found in the comedian's interjections in the video of the Lapor Pak! episode on the Trans7 YouTube channel. The interjections found include yaelah and bacot. Meanwhile, in terms of meaning, there are 11 denotative and 3 connotative meanings. Therefore, knowing the context of slang is very important for understanding how it is used appropriately.